Hubungan Parental Meta-Emotion dengan Kemampuan Regulasi Emosi Anak Pra-Sekolah - Joana Novena Putri; Fitriani Yustikasari Lubis (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to determine the relationship between parental meta-emotion and emotion regulation on pre-school kids. In IndonesiaThe two dimensions of parental meta-emotion are emotion coaching and emotion dismissing. The independent variable in this study is emotion coaching and the dependent variable are emotion coaching and emotion dismissing. The sampling technique in this study uses purposive sampling technique with 97 mothers in Bandung City. The measuring instrument used in this study is Emotion Regulation Checklist (ERC) and Maternal Emotion Style Questionnaire (MESQ). The validity and reliability test in this study uses the Cronbach Alpha technique. The result of the validity coefficient on ERC move from 0,339 to 0,953 with reliability coefficient of a = 0,951 for liability/negativity dimension and 0,948 for emotion regulation dimension. While on MESQ move from 0,317 to 0,697 with reliability coefficient of a = 0,649 for emotion regulation dimension and 0,747 for emotion dismissing dimension. Based on data analysis, a correlation value between emotion coaching and emotion regulation is 0,139 with a significance level of 0,173 and a correlation value between emotion dismissing and emotion regulation is -0,416 with a significance level of 0,000. This shows that there is not a significant relationship between emotion coaching and emotion regulation, and also there is a significant relationship between emotion dismissing and emotion regulation on pre-school kids.